Defining the Eyre Conductivity Anomaly with the Tumby Bay MT transect. Issue 1 (1st December 2019) - Robertson, Kate; Kay, Ben; Loader, Lachlan; Heinson, Graham; Thiel, Stephan
Summary: We present results of 36 broadband magnetotelluric (MT) stations along a 70 km ENE-WSW profile across the southern Eyre Peninsula, South Australia. The transect crosses the Eyre Peninsula Anomaly (EPA), first identified by induction arrows, and visualised in 3D from AusLAMP resistivity models. The significantly smaller site spacing of the Tumby Bay MT profile compared to AusLAMP (2 km instead of 55 km) has allowed us to image the EPA in high resolution which has defined the EPA into a very conductive (< 0.1Ωm) region from depths ~2-17 km and a width of about 30 km. At greater depths (~17-22 km) the conductor becomes widespread across the transect but less conductive (~30 Ωm). On the eastern third of the profile, upper crustal conductive fluid pathways are identified and may connect to the main body of the EPA.